China in Africa: an analysis of the bilateral relations between China and Angola over the past ten years - Chaparadza, Rudo Lavender (My University, 2011)
The beginning of the 21st century coincided with China‟s “going global” strategy. During this period, China increased its engagement with many African countries and this was particularly driven by the need to secure its energy resources and markets. China‟s engagements with African countries coincided with the end of the protracted civil war in Angola which brought about a significant shift in the geopolitical dynamics in Southern Africa. During this period Angola embarked on a national reconstruction programme to repair its infrastructure which had been damaged by the war. As the country could not find any help from western countries and international financial organisations, China came to its rescue by providing large sums of oil-backed loans. As a result trade figures rose between the two with China becoming the largest importer of Angolan oil and a major player in the reconstruction of Angola, thus significantly contributing to Angola„s post-war growth. This paper will demonstrate that oil is the basis of economic ties between the two countries today and that Chinese investments in Angola, especially those in the construction sector, have positively impacted on the Angolan economy and the Angolan population at large. The study also highlights the negative effects of the relationship between the two and also makes recommendations on how both countries can maximise on the existing relationship